Economic Aspects of Subjective Attitudes towards the German Minimum-Wage Reform - Alexandra Fedorets; Carsten Schröder (FinanzArchiv, 2019)
Despite skepticism among experts about the effects of a minimum wage, there is remarkably widespread public support for such policies. Using representative survey data from 2015 and 2016, we investigate the subjective attitudes driving public support for Germany's minimum-wage reform. We find that socioeconomic characteristics and political orientations explain a minor part of the variation in attitudes, whereas beliefs that the reform will improve earnings of workers with low wages and help people to maintain or improve their overall economic situation (measured by living standards, income, hours worked, and job security) play a major role, along with experience with circumvention measures.
Keywords: 330